Muslim medical ethics : from theory to practice - Brockopp, Jonathan E., 1962-; Eich, Thomas (Studies in comparative religion (Columbia, S.C.), 2008)
Muslim Medical Ethics draws on the work of historians, health-care professionals, theologians, and social scientists to produce an interdisciplinary view of medical ethics in Muslim societies and of the impact of caring for Muslim patients in non-Muslim societies. Edited by Jonathan E. Brockopp and Thomas Eich, the book challenges traditional presumptions of theory and practice to demonstrate the ways in which Muslims balance respect for their heritage with the health issues of a modern world. Like members of many other faiths, Muslims are deeply engaged by the technological challenges posed by modern biomedicine, and they respond to those challenges with enormous creativity -- whether as patients, doctors, or religious scholars. Muslim Medical Ethics demonstrates that religiously based cultural norms often inform medical practice, and vice versa, in an ongoing discourse. The contributors map the breadth and boundaries of this discourse through discussions of contested issues on the cutting edge of ethical debates, from fertilized embryos in Saudi Arabia to patient autonomy in Toronto, from organ trafficking in Egypt to sterilization in Tanzania.